Physical therapy intervention through virtual reality in individuals with balance disability: A case study - Mauro, Audi; Lavagnini, Barrozo Amanda; De Oliveira, Perin Bruna; Presumido, Braccialli Lígia Maria [UNESP]; Naomi, Sankako Andréia [UNESP] (My University, 2015)
Balance is an ability found in most of the human activities and it is essential under a functioning view. When balance is impaired due to any brain injury, several tools may be used for its treatment. One of them is virtual reality, a tool which allows individuals to make use of their senses and natural movements during virtual games in order to promote interaction on a virtual environment. This study was performed with a volunteer from the neurology section of Universidade de Marília (Unimar) physical therapy clinic under ethics parameters, and its purpose was to measure the balance of an individual with traumatic brain injury who was involved in a treatment with use of virtual-reality games. An Xbox kinect® console was utilized for this intervention, and the selected games required the use of many physical abilities, including balance. The tests were recorded on video, and pictures were analyzed by two researchers and three evaluators. Score data from each game were obtained during the process. The data analysis was quantitative in relation with game scores and qualitative in relation with the test pictures. The results obtained from the analysis of the balance tests were: (a) in romberg's test with eyes open and eyes closed there were not significant changes; (b) in sensitive romberg's test there was improvement in balance with support in both legs; in dynamic balance test there was improvement in balance during the straight-line walk. In the statistical analysis of game data friedman's variance was found in three levels of significance (p): for each sequence in the seven days of attendance the results were p=0.0367, p=0.0281 e p=0.0136; it was considered as p<0.05 what affected significantly the performance of the volunteer. According to the results observed in the study, it was concluded that virtual reality as a therapeutic media provided improvement of the volunteer's physical balance.
Keywords: Balance; Physical therapy; Virtual reality